Microvessel occlusions alter amyloid-beta plaque morphology in a mouse model of Alzheimer’s disease - Zhang, Yuying (J Cereb Blood Flow Metab, 2019)
Vascular dysfunction is correlated to the incidence and severity of Alzheimer’s disease. In a mouse model of Alzheimer’s disease (APP/PS1) using in vivo, time-lapse, multiphoton microscopy, we found that occlusions of the microvasculature alter amyloid-beta (Aβ) plaques. We used several models of vascular injury that varied in severity. Femtosecond laser-induced occlusions in single capillaries generated a transient increase in small, cell-sized, Aβ deposits visualized with methoxy-X04, a label of fibrillar Aβ. After occlusions of penetrating arterioles, some plaques changed morphology, while others disappeared, and some new plaques appeared within a week after the lesion. Antibody labeling of Aβ revealed a transient increase in non-fibrillar Aβ one day after the occlusion that coincided with the disappearance of methoxy-X04-labeled plaques. Four days after the lesion, anti-Aβ labeling decreased and only remained in patches unlabeled by methoxy-X04 near microglia. Histology in two additional models, sparse embolic occlusions from intracarotid injections of beads and infarction from photothrombosis, demonstrated increased labeling intensity in plaques after injury. These results suggest that microvascular lesions can alter the deposition and clearance of Aβ and confirm that Aβ plaques are dynamic structures, complicating the interpretation of plaque burden as a marker of Alzheimer’s disease progression.